Key Components of the Complement Lectin Pathway Are Not Only Required for the Development of Inflammatory Arthritis but Also Regulate the Transcription of Factor D - Holers, V. Michael; Borodovsky, Anna; Scheinman, Robert I.; Ho, Nhu; Ramirez, Joseline Ramos; Dobó, József; Gál, Péter; Lindenberger, Jared; Hansen, Annette G.; Desai, Dhruv; Pihl, Rasmus; Thiel, Steffen; et al. (Frontiers in Immunology, 2020)
The complement system plays an important role in the pathogenesis of rheumatoid arthritis (RA). Besides driving lectin pathway (LP) activation, the mannan-binding lectin (MBL)-associated serine proteases (MASPs) also play a key role in regulating the alternative pathway (AP). We evaluated the effects of N-acetylgalactosamine (GalNAc)-conjugated MASP-1 and MASP-2 duplexes in vitro and in mice with and without arthritis to examine whether knockdown of MASP-1 and MASP-2 expression affects the development of arthritis. GalNAc-siRNAs for MASP-1 and MASP-2 demonstrated robust silencing of MASP-1 or MASP-2 at pM concentrations in vitro. To evaluate the impact of silencing in arthritic mice, we used the collagen antibody-induced arthritis (CAIA) mouse model of RA. Mice were injected a 10 mg/kg dose of GalNAc-siRNAs 3x s.q. prior to the induction of CAIA. Liver gene expression was examined using qRT-PCR, and protein levels were confirmed in the circulation by sandwich immunoassays and Western blot. At day 10, CAIA mice separately treated with MASP-1 and MASP-2 duplexes had a specific reduction in expression of liver MASP-1 (70-95%, p < 0.05) and MASP-2 (90%, p < 0.05) mRNA, respectively. MASP-1-siRNA treatment resulted in a 95% reduction in levels of MASP-1 protein in circulation with no effect on MASP-2 levels and clinical disease activity (CDA). In mice injected with MASP-2 duplex, there was a significant (p < 0.05) 90% decrease in ex vivo C4b deposition on mannan, with nearly complete elimination of MASP-2 in the circulation. MASP-2 silencing initially significantly decreased CDA by 60% but subsequently changed to a 40% decrease vs. control. Unexpectedly, GalNAc-siRNA-mediated knockdown of MASP-1 and MASP-2 revealed a marked effect of these proteins on the transcription of FD under normal physiological conditions, whereas LPS-induced inflammatory conditions reversed this effect on FD levels. LPS is recognized by Toll-like receptor 4 (TLR4), we found MBL not only binds to TLR4 an interaction with a Kd of 907 nM but also upregulated FD expression in differentiated adipocytes. We show that MASP-2 knockdown impairs the development of RA and that the interrelationship between proteins of the LP and the AP may extend to the transcriptional modulation of the FD gene.